Efeitos da previdência rural na agricultura familiar da microrregião Serra de São Miguel - RN - Souza, Ronie Cléber de (2012)
The objective of the present work is to verify the effects of Rural Social welfare in the family agriculture of the microrregião Serra de São Miguel-RN. The study based on available bibliography on the theme, in secondary data and in a rising amostral accomplished in three municipal districts (Encanto, São Miguel and Riacho de Santana) of the microrregião. The universe of the study was the establishments of the family agriculture appeared in the Agricultural Census of 2006, in those municipal districts. The unit of considered analysis was the rural family, with the interviews being applied close to the farmers' families with and without retired rural. The sample was of 94 present families in the family establishments. The results demonstrate that the Rural Precaution reaches a significant covering degree in the rural area of the researched municipal districts, with an average of 1,57 beneficiaries for home in the families with retired. The data of the research attest that the family agriculture in the microrregião Serra de São Miguel-RN it has few favorable conditions for his/her development, once, besides the shortage of lands and of the climatic factor of the area, the returned public politics the family farmers' totality - like PRONAF and PAA -, it has been unable to give effective answers for the improvement of the life conditions in the rural way, have seen the minimum amount of families reached by those politics, be in function of the drawing or of the atmosphere where they are done. In this context, he/she stands out the importance of the Rural Precaution that, in function of the application of the constitutional devices that you/they guaranteed his/her universalization, it has been the only relevant public politics that, in fact, it has been reaching her/it all their beneficiary potentials. Given the general situation of the family agriculture of the microrregião and of the specific characteristics of the researched family establishments, the hypothesis was corroborated that the rural retirement doesn't contribute directly to the increase / making possible of the family agriculture. In spite of 57,4% of the families with retired have declared to use resources of the retirement in the costing of the rural activity carried out by the family, the annual medium value of the expense just located around 7,02% of the annual value of the retirements gained by the families in the year of 2010. Data the low levels in that the social reproduction of the great majority of the family establishments of the microrregião, the maintenance of the families is operated represents the main destiny of the resources precautions. It was also confirmed the hypothesis that the Rural Precaution constitutes the main monetary contribution of the families with retired. For more than 93% of the families with retired, the retirements doing 50% or more of the total of the family monetary income, and in the composition of the rural income of the families with retired and pensioners, the originating from income the rural retirements are equal to 65,24% of the total of the annual income obtained by the families. It is ended, because, that the rural precaution, given to the adversities for the development of the family agriculture, of the operational inefficacy of the public politics and of the few opportunities of generation of existent income in the local savings, it is the main responsible for the reduction of the poverty and, consequently, for the improvements of the conditions of life of the families of and with seniors in the rural way of the microrregião Serra de São Miguel-RN